Serum Lipid Profiles in Hypertensive Diabetes Mellitus Type 2 Patients. - Hashim, Dena A (Al-Nahrain Journal of Science, 2018)
This study was designed to determine the relationship between the levels of lipid profile in diabetes mellitus type 2 and hypertension. Blood samples were collected from patients under 40 years old with diabetes type 2 and suffering from hypertension. Lipid profile was determined enzymaticlly by using kits. Results revealed that the level of cholesterol was significantly increased in diabetic patients with hypertension more than diabetic patients only. Also the level of triglyceride (TG) was significantly higher in patients suffering from diabetes with hypertension than patients suffering from diabetes only. A significant decrease in the level of high density lipoprotein was recorded in diabetes patients who are suffering from hypertension than patients with diabetes only. There was asignificant increase in the level of triglyceride (TG), low density lipoprotein (LDL) and very low density lipoprotein (VLDL) in male than female patients.